Effect Training Passing Futsal: ACTIVE AND PASSIVE TRAINING - Chairul Umam Ramadhan (Universitas Suryakancana, 2024)
Futsal has become one of the popular sports games among people today, including students in middle schools who participate in the Futsal Extracurricular Program to nurture and develop their interests and talents. Naturally, participants must master fundamental futsal techniques, including Passing. This study aims to explore the impact of active and passive passing drills on improving basic passing skills in futsal games. The study's target population consists of participants from the Futsal Extracurricular Program at Insan Cendekia Arrasyid Middle School. The sample employed a total sampling method, involving 16 participants to match the population size. The research was conducted at the futsal field of Insan Cendekia Arrasyid Middle School. The research method employed is an experimental approach utilizing a Two Group Pretest-Posttest Design. During the implementation, participants were subjected to an initial assessment followed by a treatment involving a combination of active and passive passing drills with variations, and finally, a concluding assessment was conducted. Based on the research outcomes, data processing, data analysis, and hypothesis testing, a significant influence was detected in enhancing basic passing skills in futsal among participants in the Futsal Extracurricular Program at Insan Cendekia Arrasyid Middle School, as indicated by the results of t=2.890 and sig=0.019<0.05. Therefore, the null hypothesis (Ho) was accepted. This outcome signifies that there is a notable improvement attributed to active and passive training techniques on fundamental passing skills in futsal among participants in the Futsal Extracurricular Program at Insan Cendekia Arrasyid Middle School.